1987
DOI: 10.1007/bf01400516
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of phenytoin and its enhanced action by combined administration with mannitol and vitamin E in cerebral ischaemia

Abstract: To study the therapeutic effect of phenytoin on cerebral ischaemia and confirm whether or not the effectiveness of phenytoin could be enhanced by combined administration with free radical scavengers, twenty-five dogs were subjected to ischaemia, using the "canine model of the completely ischaemic brain regulated with a perfusion method". Five animals served as untreated controls, fifteen received treatment with several doses of phenytoin and five were treated with 10 mg/kg phenytoin, 2 g/kg mannitol and 30 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
4

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 33 publications
2
5
0
4
Order By: Relevance
“…The protective effect of PHT against ischemic brain damage (Cullen et al, 1979;Fukuda et al, 1983;Suzuki et al, 1987) and kainate-induced neurotoxicity (Zaczek et al, 1978) in vivo agreed with our present results. No protective effect of PHT was found against glutamateinduced neurotoxicity in cortical cell culture (Koh and Choi, 1987a).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…The protective effect of PHT against ischemic brain damage (Cullen et al, 1979;Fukuda et al, 1983;Suzuki et al, 1987) and kainate-induced neurotoxicity (Zaczek et al, 1978) in vivo agreed with our present results. No protective effect of PHT was found against glutamateinduced neurotoxicity in cortical cell culture (Koh and Choi, 1987a).…”
Section: Discussionsupporting
confidence: 95%
“…Also, PHT is indicated to block glutamate receptors (Matthews and Connor, 1977;Sastry and Phillis, 1976) though there have been conflicting reports (McLean and Macdonald, 1983;Nicoll and Wojtowicz, 1980). Several investigators reported that PHT protected the neurons of dogs (Suzuki et al, 1987) and rabbits (Cullen et al, 1979) against cerebral ischemia. However, they did not consider PHT as a glutamate blocker probably because the PHT blockage of glutamate receptors had been doubtful.…”
Section: Introductionmentioning
confidence: 94%
“…The doses of TM, MP and vitamin E were selected on the basis of previous studies. 13,47,48 Our experimental study demonstrated that all three treatment regimens decreased the level of LP following spinal cord trauma in rats. Vitamin E was less e ective than TM and MP.…”
Section: Discussionmentioning
confidence: 68%
“…A variety of other approaches to protect the injured spinal cord from secondary pathological processes have been examined experimentally, including antioxidants, membrane stabilizers, glutamate antagonists, anti-inflammatories, caspase inhibitors, calpain inhibitors and other compounds of uncertain mechanism [15]. During the past decade, considerable research efforts have been focused on the role of free radicals in the occurrence of ischemic damage [16,17]. In this study, ascorbic acid and alphatocopherol known as free radical scavengers were used to investigate their efficacy in the functional recovery of spinal cord injured rats.…”
Section: Introductionmentioning
confidence: 99%